Les pratiques enseignantes mises en récit - Jean-François Marcel (Recherches en Éducation)
This methodology-oriented article presents a study of teachers’ practices along five steps. Based on stories, it calls for the interest in reconciling action and story. This approach mobilizes observation devices and interviews and defends the use of three different stories (the story of the observer, the story of the teacher and the story of the practices according to the principle of double reading), each structured by a narrative pattern. The article also analyzes the epistemological foundations of this method through a theoretical clarification of “teacher practices”, which in connection with the work of OPEN, leads to a quaternary model and clarifies research orientations and standpoints in connection with the researcher’s engagement.